Eczema-related Web Search Data in Sweden: Investigating Search Patterns and the Influence of Weather - Linda Tizek; Hannah Wecker; Simon Schneider; Emma K. Johansson; Yodit Girmay; Alexander Zink (Medical Journals Sweden, 2022)
As atopic eczema is triggered by environmental factors, such as temperature, differences in disease burden between and within countries are possible. One method to study this phenomenon is to perform web-search analysis, since the internet is commonly used to retrieve health-related information. This study, investigating the Google search volume regarding eczema in Swedish counties between April 2017 and March 2021, revealed a continuous increase in number of searches and that the search volume was higher in Northern than Southern Sweden. Gotland had the most searches per 100,000 inhabitants. In general, there was a negative correlation between search volume and temperature (r=-0.315, p < 0.001) and hours of sunshine (r=-0.213, p < 0.001), whereas there was a positive association between search volume and wind (r=0.229, p < 0.001). Search engine analysis is a rapid and cost-effective method of examining search behaviour regarding disease among the general population within a country and, thus, can enable the identification of regions with specific interests and needs.